L'agriculture périurbaine face aux vulnérabilités foncières en Algérie - Bouziane Semmoud; Abdelhamid Ladhem (Territoire en Mouvement)
Rural periurban spaces in major Algerian cities are going through changes which are due to three combined factors that can sometimes appear as contradictory: liberal opening, oil revenue redistribution and the evolution of urban areas and markets. The diversity and contrasts of those spaces are highlighted by the examples of Central Mitidja (located between Blida and Algiers) and Oran area. The approach that resulted from non-directive interviews and life stories with former and new farmers illustrates those recent changes: agrarian fragmentation, land transactions, intensified farming, changes in modes of tenure, submission to a deregulated urban market and so on… This approach underlines their agrarian vulnerabilities, the various dynamic adjustment strategies for some, and the inertia and fragility of others. The agricultural deployment through intensification appears as heterogeneous, fragile and little environmentally-friendly. It is equally triggered and forced by urban expansion, backed up by state funding but also structured by private urban actors.